Exosomal miR-452-5p Induce M2 Macrophage Polarization to Accelerate Hepatocellular Carcinoma Progression by Targeting TIMP3 - Hu Zongqiang; Chen Jiapeng; Zhao Yingpeng; Yan Chuntao; Wang Yiting; Zhu Jiashun; Li Li (Journal of Immunology Research, 2022)
Background. Hepatocellular carcinoma (HCC) cell-derived exosomes have shown effects on inducing M2 macrophage polarization and promoting HCC progression. MiR-452-5p was reported by recent studies to promote malignancy progression as an exosomal microRNA that secreted by HCC cells, of which the underlying mechanism remains unclear. Here, we further explored how miR-452-5p functions in HCC. Methods. MiR-452-5p expressions in HCC cells was examined by in situ hybridization. Next, HCC cell lines were transfected with the mimics or the inhibitor of miR-452-5p. Transfected cells’ biological behavior were analyzed by CCK-8, flow cytometry, and Transwell assay. Then, exosomes were purified from miR-452-5p inhibited or overexpressed HCC cells and cocultured with macrophages to examine the role of miR-452-5p in macrophage polarization. To examine the role of exosomal miR-452-5p on macrophage polarization and tumor growth. We also performed the dual-luciferase assay to explore the targeting relationship between miR-452-5p and TIMP3. Results. The upregulation of miR-452-5p was identified in HCC. The effects of HCC cell-derived exosomes on accelerating HCC migration and invasion and inducing M2 macrophage polarization were confirmed, which were further enhanced after overexpressing miR-452-5p but neutralized after silencing miR-452-5p. In addition, in vivo experiments demonstrated the effect of miR-452-5p on accelerating HCC growth and metastasis. Also, we identified that TIMP3 overexpression inhibited the promoted cell invasion and migration by HCC cell-derived exosomes. Conclusion. Exosomal miR-452-5p secreted from HCC cells could induce polarization of M2 macrophage and therefore stimulating HCC progression by targeting TIMP3. Thus, miR-452-5p might be a potential biomarker for HCC prognosis.